Phenomenological Views of Pancasila Perspectives about Democracy - Iskandarsyah Siregar (Polit Journal Scientific Journal of Politics, 2023)
As Indonesia navigates its complex path towards economic and political modernization, the transition to democracy has seen it evolve into an industrial society. However, this change has inadequately empowered vital economic sectors for public welfare. Additionally, the nation's unstable democratic politics stray from Pancasila, Indonesia's guiding philosophical principles advocating for deliberative dialogue. Over the past 15 years, developmental politics and political liberalization have clashed, undermining both the collective economy and cultural wisdom, and eroding Indonesia's unique cultural identity. This has stirred doubts about the fit of democracy within Indonesia's nation-state construct. The ensuing research aims to reevaluate indigenous wisdom and political ideologies ingrained in Indonesia's diverse ethnic landscape, focusing on untapped social capital to bolster the democratic framework. The study comprises two key research areas: one looks at ethnic communities like Wajo and Minang, and the second studies social dynamics in various Java city parks. Grounded in Consultative Democracy and examined through a phenomenological lens, the research sits within the broader arena of political anthropology. It uses a qualitative-interpretive methodology to delve into culture, economics, and politics, aspiring to enrich our understanding of their intricate interconnections in modern Indonesia and contribute to a nuanced dialogue on Indonesia's democratic viability